Schizophrenia: Current and Perspectives - Melika Ahangar; Ali Mohammad Ahadi; Fatemeh Moradi (Journal of Medical Biomedical and Applied Sciences, 2021)
Schizophrenia is one of the most prevalent nervous system related disorders with a severe and progressive symptoms. Main target population of this disease is the people after 60 years old. Several etiological factors are involved in Schizophrenia pathogenesis including: trauma, stroke, central nervous system viral infection, genetic and epigenetics elements. We focus here onmolecular biology aspect of schizophrenia manifestation. New findings about pathogenesis of this disease and pathways deal with schizophrenia will present in this review and finally we propose here some probable strategies applicable for treatment of this disorder.